NUMERICAL SIMULATION of THE BEHAVIOR of THE BEHAVIOR of REINFORCED CONCRETE BEAMS and COLUMNS BY FEM CAASTEM 2000 PROGRAM - da Costa Jacomassi, Luciana Marques [UNESP]; Barbosa, Monica Pinto; Gamino, Andre L. [UNESP] (Univ Politecnica Catalunya, 2009)
The objective of this paper is the numerical study of the behavior of reinforced concrete beams and columns by non-linear numerical simulations. The numerical analysis is based on the finite element method implemented in CASTEM 2000. This program uses the constitutive elastoplastic perfect model for the steel, the Drucker-Prager model for the concrete and the Newton-Raphson for the solution of non-linear systems. This work concentrates on the determination of equilibrium curves to the beams and force-strain curves to the columns. The numeric responses are confronted with experimental results found in the literature in order to check there liability of the numerical analyses.
Keywords: non-linear analysis; FEM; R/C beams; R/C columns